Using quartz sand to enhance the removal efficiency of M. aeruginosa by inorganic coagulant and achieve satisfactory settling efficiency. Issue 1 (December 2017) - Pei, Haiyan; Jin, Yan; Xu, Hangzhou; Ma, Chunxia; Sun, Jiongming; Li, Hongmin
Abstract In this study, low-cost and non-polluting quartz sand was respectively mixed with AlCl3, FeCl3 and PAFC to synergistically removeMicrocystis aeruginosa . Results showed that quartz sand could markedly increase the algae removal efficiency and decrease the coagulant doses. The increase of removal efficiency with AlCl3 and FeCl3 was only due to the enhancement of floc density by the quartz sand. However, the removal efficiency with PAFC was increased not only by the enhanced floc density, but also by the enlarged floc size. Flocs from 50 mg/L sand addition were larger than that with other sand doses, which was on account of the appropriate enhancement of collision efficiency at this dose. After coagulation, the extracellular organic matter (EOM) and microcystins (MCs) in system with quartz sand was remarkably reduced. That's because quartz sand can enhance the coagulation so as to improve capping the EOM and MCs in flocs during coagulation process. Owing to 200 mg/L quartz sand could damage the cell's membrane during coagulation proces, algal cells in the system lysed two days earlier than with 50 mg/L sand during flocs storage. In addition, cells with PAFC incurred relatively moderate cellular oxidative damage and could remain intact for longer time.